ANALISIS MODEL MODAL SOSIAL TERHADAP KEBERDAYAAN PETANI KARET DI KECAMATAN TAMBUSAI UTARA - Antonius Cosnami Sitorus; Ahmad Rifai; Kausar Kausar (Fakultas Pertanian, Universitas Riau, 2017)
The objectives of this research were to (1) analyze the social capital; (2) analyze the empowerment of the rubber farmers and (3) analyze the relationship between social capital and empowerment of rubber farmers. The research was conducted in North Tambusai sub-district in Rokan Hulu regency. The rubber farmer sample was taken purposively in two villages that were involving 60 rubber farmers. The social capital and empowerment of rubber farmers was measured by Likert scale, and the relationship between social capital and empowerment of the rubber farmers was examined by Spearman rank correlation analysis. The result showed that the networking, trust and norm were strong ties in social capital of the rubber farmers. The families, neighborhoods, and business partners were strong tie builders to three elements of the social capital, which are social networking, trust, and social norm, while the government and community leader were weak tie builders to three elements of the social capital of the rubber farmers. The rubber farmers was powerless both socially and economically. The social powerless condition was depicted by rubber farmers’ weakness in accessing extension information, health services, and social security. The economical powerless condition was depicted by weak access to capital, educations, production inputs, and the household access to electricity, gas, clean water, exception market access. Significant positive correlation was found between the social capital and the empowerment of rubber farmers. This study suggests that the government role is needed to build stronger social networking of the rubber farmers to the business partners.